Sodom and Gomorrah - Proust, Marcel, 1871-1922 (Proust, Marcel, 1871-1922. À la recherche du temps perdu., 2021)
Marcel Proust's 'In Search of Lost Time' is considered by many to be the greatest novel of the twentieth century. The fourth volume, 'Sodom and Gomorrah', is notable for its pioneering discussion of homosexuality. After publication, Colette wrote Proust: "No one has written pages such as these on homosexuals, no one!" This edition is edited and annotated by Proust scholar William C. Carter, who endeavors to bring the classic C.K. Scott Moncrieff translation closer to the spirit and style of the original.